Analysis of Students' Critical Reading Ability in Science Learning Using the Argument-Based SQ3R Method - Heriana, Dena Emarani; Hartono, Hartono; Isnaeni, Wiwi (Journal of Innovative Science Education, 2023)
The challenges that students will face in the future are complex, so students need a myriad of competencies. To be able to compete and face challenges in the industrial era 4.0, one of which is the ability to process information and communicate. This study aims to analyze the effect of the argument-based SQ3R method in improving students' critical reading skills in science learning. This research is a Quasi-Experimental study with a randomized pretest-posttest control group design. The research sample consisted of 62 class VIII students consisting of two classes. The technique for collecting data on reading interest used a questionnaire sheet instrument and data on the results of students' critical reading ability used essay questions. Based on the results of the research data analysis, it was shown that the argument-based SQ3R learning method had a positive effect on students' critical reading skills, with the results of the t-test showing Asymp. sig. of 0.00 <0.05, with supporting data on students' critical reading skills seen from the student's reading interest questionnaire with the results of the Mann Whitney U-test showing Asymp. Sig of 0.018 <0.05 which means that there is an influence of the argument-based SQ3R learning method on students' critical reading skills.